Cause analysis of coal mine burst accident based on text mining - Jiajia WANG; Zhenhua OUYANG; Haoran GUO; Wenshuai LI; Qianhai XU; Xinwen YANG (Meikuang Anquan)
With the increase of mining depth of coal resources, rock burst has become one of the main disasters threatening the safety production of coal mines. In-depth analysis of rock burst accidents and mining factors causing disasters are extremely important to achieve accurate prevention and control of rock burst and scientific management. Based on big data, text mining technology is used to excavate the causes of 29 rock burst accidents, analyze the importance of each cause of rock burst accidents, study the correlation between various disaster factors, from the three aspects of geological environment, mining technology and personnel management, the whole process and multi-angle rock burst prevention countermeasures are proposed respectively for the production before, during and after production. The results show that: the TF-IDF values (word frequency-inverse text frequency) of the disaster factors include fault, hard thick roof, large buried depth, geological environment factors such as impact tendency of coal seam and its roof and floor, stress superposition, earthquake, the TF-IDF values of mining disturbance, mining technology factors such as goaf, coal pillar and island working face, the TF-IDF valuesof personnel management factors such as lack of disaster awareness, lax safety management, inadequate technical management, inadequate pressure relief measures, and unreasonable labor organization are all high, indicating that the occurrence of rock burst accidents is caused by geological environment, mining technology, personnel management and other factors. In the network of causes of rock burst accidents, the key causes of rock burst accidents are fault, mining disturbance, lack of understanding of disaster, goaf, hard thick roof, large buried depth, coal seam and its roof and floor with impact tendency. The occurrence of rock burst accident is not only caused by a single disaster factor, but also caused by a variety of disaster factors.